Low-Rise Housing Construction: Incentives for Development, Internal Control - Natalia V. LAZAREVA; Elena N. SHTYKOVA (Communications of International Proceedings, 2020)
In the study, the authors examined the current trends in the development of low-rise housing construction (hereinafter referred to as MEHS) in Russia and in the countries of the European Union (hereinafter referred to as the EU) in the context of the global economic recession in 2020. On the example of foreign experience, the prospects for the development of MEZhS in Russia are proved. The factors hindering its development are identified, recommendations are given to eliminate the negative influence of these factors with continuous internal control of risks. A classification of low-rise buildings is carried out, an analysis of the dynamics of construction volumes, commissioning, the share of MEZhS in the total volume of housing construction is carried out, analogies are drawn between MEZhS in Russia and in the EU countries to identify incentives for further development.
Keywords: low-rise housing construction (MEZhS); individual housing construction (IZhS); development incentives; internal control